PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V UPT SD NEGERI 060971 KEMENANGAN TANI TAHUN PEMBELAJARAN 2025/2026 - Reh Syerina Br Bangun; Ester Julinda Simarmata; Paska Sriulina Tarigan; Reflina Sinag; Eka Margareta Sinaga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model on the IPAS learning outcomes of Grade V students at UPT SD Negeri 060971 Kemenangan Tani in the 2025/2026 academic year. This study employed a quantitative method with a one-group pretest-posttest design, involving 25 students as the sample. Data collection techniques included tests, questionnaires, observations, and documentation. The results of the study showed that the pretest results in Grade V had an average score of 57, which was categorized as low, while the posttest average score increased to 85.04, which was categorized as high. Furthermore, hypothesis testing using the t-test obtained a t-value greater than or equal to the t-table value, namely 22.876 ≥ 2.069. Therefore, it can be concluded that the implementation of the Problem Based Learning (PBL) model significantly improves students’ learning outcomes in the IPAS subject.